Oxidative Functionalization of Cyclic N-Arylamines with Nitromethane and TMSCN Using the T-HYDRO/t-BuOK System - Rao, Gunda Ananda; Periasamy, Mariappan (Synthesis, 2018)
Tertiary cyclic N-arylamines react with nitromethane in the presence of the tert-butyl hydroperoxide (T-HYDRO)/t-BuOK system to give β-nitroamines in up to 90% yield. When TMSCN is used in place of nitromethane, α-aminonitriles are obtained in up to 96% yield. The method is suitable for several unactivated cyclic arylamine substrates. These transformations are rationalized considering the formation of the corresponding iminium ion intermediates via an initial electron transfer process.
Keywords: N-arylamines; iminium ions; enamines; α-aminonitriles; β-nitroamines